Secretagogin as a marker to distinguish between different neuron types in human frontal and temporal cortex - Tapia-González, Silvia; DeFelipe, Javier (Frontiers in Neuroanatomy, 2023)
The principal aim of the present work was to chemically characterize the population of neurons labeled for the calcium binding protein secretagogin (SCGN) in the human frontal and temporal cortices (Brodmann’s area 10 and 21, respectively). Both cortical regions are involved in many high cognitive functions that are especially well developed (or unique) in humans, but with different functional roles. The pattern of SCGN immunostaining was rather similar in BA10 and BA21, with all the labeled neurons displaying a non-pyramidal morphology (interneurons). Although SCGN cells were present throughout all layers, they were more frequently observed in layers II, III and IV, whereas in layer I they were found only occasionally. We examined the degree of colocalization of SCGN with parvalbumin (PV) and calretinin (CR), as well as with nitric oxide synthase (nNOS; the enzyme responsible for the synthesis of nitric oxide by neurons) by triple immunostaining. We looked for possible similarities or differences in the coexpression patterns of SCGN with PV, CR and nNOS between BA10 and BA21 throughout the different cortical layers (I–VI). The percentage of colocalization was estimated by counting the number of all labeled cells through columns (1,100–1,400 μm wide) across the entire thickness of the cortex (from the pial surface to the white matter) in 50 μm-thick sections. Several hundred neurons were examined in both cortical regions. We found that SCGN cells include multiple neurochemical subtypes, whose abundance varies according to the cortical area and layer. The present results further highlight the regional specialization of cortical neurons and underline the importance of performing additional experiments to characterize the subpopulation of SCGN cells in the human cerebral cortex in greater detail.